2019
DOI: 10.3390/molecules24081522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biogenic Amines in Chinese Commercial Soy Sauces

Abstract: Soy sauce contains a series of biogenic amines (BAs) which is a kind of bioactive organics relating to food quality and safety. High concentration of BAs may lead to remarkable physiological and toxicological influences on human bodies, including hypotension, dizziness, and headaches. Here, we systematically compared the levels of ten main BAs among 53 Chinese commercial soy sauces using an improved high-performance liquid chromatography (HPLC) method. The results showed that the brands and production regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…BAs are organic compounds with biological activity that result from the decarboxylation of precursor amino acids caused by microorganisms' amino acid decarboxylases [51]. Therefore, the contents of precursor amino acids are highly likely to affect the production of biogenic amines by microorganisms.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…BAs are organic compounds with biological activity that result from the decarboxylation of precursor amino acids caused by microorganisms' amino acid decarboxylases [51]. Therefore, the contents of precursor amino acids are highly likely to affect the production of biogenic amines by microorganisms.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%
“…BAs are biologically active organic compounds formed from the decarboxylation of precursor amino acids by the action of amino acid decarboxylases produced by microorganisms [29]. As a result, the levels of precursor amino acids are highly likely to influence the production of biogenic amines by microorganisms.…”
Section: Amino Acid Metabolic Pathwaysmentioning
confidence: 99%
“…reported that tyramine was the most prevailing amine in soy sauce followed by spermidine, histamine, and cadaverine with a total content of 41.7–1357 mg/L [ 50 ]. Other works have reported total content of 56–634 mL/L for soy sauce [ 51 ]; 30–82 mg/kg for tofu with spermidine being the most abundant [ 52 ]. Fermented cabbage known as sauerkraut also contains BAS specifically, histamine, tyramine, putrescine, cadaverine, spermine, and spermidine [ 53 ].…”
Section: Biogenic Amines In Foodsmentioning
confidence: 99%